Development of a Speed Training Model Using Running with the Ball Technique for football Athletes Aged 15–17 Years - Julio Roberto; Muhammad Maulana Fajar (Journal Physical Health Recreation (JPHR), 2026)
This study developed a speed training model of the running with the ball technique of football athletes aged 15–17 years. The study is based on physical test data over the past five years on North Sumatra PPLP athletes which shows that most of the athletes are in the medium and low speed categories. This research uses the Research and Development (R&D) method adapted from the Borg and Gall models. The research subjects consisted of 52 athletes from four football clubs in Medan City. The research stages include needs analysis, product design, small group trials (12 athletes), product revisions, large group trials (40 athletes), and final evaluation. Data collection techniques through observation, interviews, questionnaires, and speed tests. The results of the study were in the form of 15 speed training models based on the running with the ball technique which were declared valid and feasible based on the results of expert validation and athlete responses. The developed training model has been proven to be effective in improving athletes' motivation, participation, and speed performance in contextual match situations.